Para além do movimento maker: um contraste de diferentes tendências em espaços de construção digital na Educação - Silva, Rodrigo Barbosa e (2017)
Spaces dedicated to construction based on digital resources are taking part of public and private educational projects in Brazil as a result of the growing public interest in hands-on activities. These spaces are planned, built, and executed under transnational trends of digital construction. This Ph.D. thesis contrasts maker proposals, e.g. FabLabs, Maker Media, criticism to the Californian tecnoutopia, and FabLearn, in order to comprehend the origins, the aims and the implications of each one of these distinct proposals of technologies in Education. One considering the under-theorization of maker movement in general, which privileges the ´making´ over reflection, this thesis presents concepts of technology based on Alvaro Vieira Pinto, and praxis and freedom on Paulo Freire’s work, along a discussion of social basis of techniques on Science, Technology and Society Studies. It is a descriptive research about facts and phenomenons in an ongoing debate about Brazilian techno science and education. As results, it presents firstly a critical reflexive approach of diverse maker proposals, secondly a contribution to progressive education discussions, and thirdly the enrichment and expansion of national thinkers’ theories on technology and education. It concludes that FabLearn is consistent with Freire’s ideas of progressive education, and Alvaro Vieira Pinto’s philosophical and Paulo Freire’s educational thoughts can be filled in, based on an emancipatory and inclusive perspective of society, the theoretical gap of maker movement.